2018
DOI: 10.2147/ijn.s168148
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled biodegradable polymeric micelles to improve dapoxetine delivery across the blood–brain barrier

Abstract: BackgroundDapoxetine (DPX) is the drug of choice for the specific treatment of premature ejaculation. DPX is characterized by relatively low bioavailability (42%) and short half-life (1.5 h). The aim of this study was to improve DPX bioavailability and delivery across the blood–brain barrier (BBB) using a nanostructured DPX formulation for improved DPX efficacy and patient satisfaction.Materials and methodsDPX-loaded polymeric micelles (PMs) formulations (F1–F3) were characterized for particle sizes, entrapmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Dubey et al [43] demonstrated increased vesicle size of ethosomes with increasing PL content. In another study, Ahmed and Badr-Eldin [44] reported an increase in avanafil invasome size with increasing PL content of the vesicles. Regarding the HLB of the surfactant, it was observed that a significant reduction of the vesicle size occurs as the HLB is decreased.…”
Section: Discussionmentioning
confidence: 89%
“…Dubey et al [43] demonstrated increased vesicle size of ethosomes with increasing PL content. In another study, Ahmed and Badr-Eldin [44] reported an increase in avanafil invasome size with increasing PL content of the vesicles. Regarding the HLB of the surfactant, it was observed that a significant reduction of the vesicle size occurs as the HLB is decreased.…”
Section: Discussionmentioning
confidence: 89%
“…Poly(ethylene glycol)-b-poly(lactide-co-glycolide) (PEG-b-PGLA) seems to be a promising DDS [120][121][122], capable of passing the blood brain barrier [123,124]. Liu et al [125] investigated PEG 2000 / 5000 -b-PLGA (different ratio's) micelles on their biocompatibility and indicated that all micelles presented very low cytotoxicity.…”
Section: Peg-b-plgamentioning
confidence: 99%
“…The prepared VNP-TPGS-ALA dispersion was investigated for mean particle size by light scattering technique using a Zetatrac particle size analyzer (Microtrac Inc., Montgomeryville, PA, USA). 28…”
Section: Evaluation Of Vnp-tpgs-ala Micelles Particle Sizementioning
confidence: 99%